2021
DOI: 10.3389/fmars.2021.679913
|View full text |Cite
|
Sign up to set email alerts
|

Integrating High-Resolution Coastal Acidification Monitoring Data Across Seven United States Estuaries

Abstract: Beginning in 2015, the United States Environmental Protection Agency’s (EPA’s) National Estuary Program (NEP) started a collaboration with partners in seven estuaries along the East Coast (Barnegat Bay; Casco Bay), West Coast (Santa Monica Bay; San Francisco Bay; Tillamook Bay), and the Gulf of Mexico (GOM) Coast (Tampa Bay; Mission-Aransas Estuary) of the United States to expand the use of autonomous monitoring of partial pressure of carbon dioxide (pCO2) and pH. Analysis of high-frequency (hourly to sub-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…The effects of seasonal temperature change on pCO 2 in the deconvolution were like those seen in pCO 2 monitoring across several United States estuaries (Joesoef et al, 2015;Rosenau et al, 2021) who used similar analytical methods to separate the effects of temperature and aggregated metabolism/mixing on pCO 2 . Like those studies, we did not quantitatively separate the metabolic and mixing effects.…”
Section: Attributing Factors Controlling Carbonate and Oxygen Variationmentioning
confidence: 79%
See 2 more Smart Citations
“…The effects of seasonal temperature change on pCO 2 in the deconvolution were like those seen in pCO 2 monitoring across several United States estuaries (Joesoef et al, 2015;Rosenau et al, 2021) who used similar analytical methods to separate the effects of temperature and aggregated metabolism/mixing on pCO 2 . Like those studies, we did not quantitatively separate the metabolic and mixing effects.…”
Section: Attributing Factors Controlling Carbonate and Oxygen Variationmentioning
confidence: 79%
“…We observed the NE shelf region to have pCO 2 at near-equilibrium or slightly below atmospheric levels and pH close to 8.1, with little seasonal variability, but larger pCO 2 and pH variations were routinely observed further into the Hauraki Gulf, and especially toward the inner Firth. It was clear that carbonate conditions at the Firth were responding to more complex conditions than those for the open NE shelf, as described for other systems in proximity to the land-sea interface (Provoost et al, 2010;Joesoef et al, 2015;Rosenau et al, 2021). Among these conditions are freshwater effects (Carstensen and Duarte, 2019;Van Dam and Wang, 2019).…”
Section: Attributing Factors Controlling Carbonate and Oxygen Variationmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies have confirmed that the combination of physical and biological processes in coastal ecosystems causes strong diurnal variability in carbonate chemistry: the diurnal amplitudes for pCO 2 and pH in many shallow coastal areas are 10~100 times higher than that in the open ocean (Carstensen and Duarte, 2019;Rosenau et al, 2021;Torres et al, 2021). This high temporal variability creates significant challenges for detecting OA changes (Carter et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, most studies of ecosystem metabolism in estuaries have focused either on high frequency O 2 measurements or less frequent, lower resolution pH or carbon measurements. There has been little focus on high frequency and high-resolution measurements of both O 2 and pH (Rosenau et al, 2021) coupled with measurements of carbonate chemistry. Studies that have focused on the monitoring of high frequency carbonate chemistry in coastal environments (Baumann et al, 2015;Saderne et al, 2015;Wang et al, 2015), have lacked simultaneous comparisons of distinct habitats.…”
Section: Introductionmentioning
confidence: 99%